2017
DOI: 10.1098/rspb.2017.1364
|View full text |Cite
|
Sign up to set email alerts
|

Changes in predator exposure, but not in diet, induce phenotypic plasticity in scorpion venom

Abstract: Animals embedded between trophic levels must simultaneously balance pressures to deter predators and acquire resources. Venomous animals may use venom toxins to mediate both pressures, and thus changes in this balance may alter the composition of venoms. Basic theory suggests that greater exposure to a predator should induce a larger proportion of defensive venom components relative to offensive venom components, while increases in arms races with prey will elicit the reverse. Alternatively, reducing the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…Venomous anthozoans often elaborate the same combination and potency of toxins for both predation and defense, potentially where constitutive expression is adequate for both purposes, even during a severe “bleaching” event causing an enhance requirement for heterotrophic metabolism (Hoepner, Abbott, & Burke da Silva, ). Changes in predator exposure, but not diet, elicit a larger venom proportion of defensive toxins than predatory toxins in the scorpion Liocheles waigiensis (Gangur et al, ), and remarkably, carnivorous cone snails are reported to switch between distinct venoms in response to predatory or defensive stimuli (Duterte et al, ). The only known predators of T. coccinea in the tropical Indo‐Pacific are the gastropod Epidendrium billeeanum (Rodríguez‐Villalobos, Ayala‐Bocos, & Hernandez, ) and the nudibranch Phyllida melanobrachia (Okuda, Klein, Kinnel, Li, & Scheuer, ), while generalist predators are yet to be detected within invaded habitats of the southwestern Atlantic (Moreira & Creed, ).…”
Section: Discussionmentioning
confidence: 99%
“…Venomous anthozoans often elaborate the same combination and potency of toxins for both predation and defense, potentially where constitutive expression is adequate for both purposes, even during a severe “bleaching” event causing an enhance requirement for heterotrophic metabolism (Hoepner, Abbott, & Burke da Silva, ). Changes in predator exposure, but not diet, elicit a larger venom proportion of defensive toxins than predatory toxins in the scorpion Liocheles waigiensis (Gangur et al, ), and remarkably, carnivorous cone snails are reported to switch between distinct venoms in response to predatory or defensive stimuli (Duterte et al, ). The only known predators of T. coccinea in the tropical Indo‐Pacific are the gastropod Epidendrium billeeanum (Rodríguez‐Villalobos, Ayala‐Bocos, & Hernandez, ) and the nudibranch Phyllida melanobrachia (Okuda, Klein, Kinnel, Li, & Scheuer, ), while generalist predators are yet to be detected within invaded habitats of the southwestern Atlantic (Moreira & Creed, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests scorpions can modify their venom composition in response to predator exposure (Gangur et al, 2017). Repeated periodical encounters with a surrogate vertebrate predator (a taxidermied mouse) over a 6 week period led Hormurus waigiensis to appear to produce a higher relative abundance of some vertebrate specific toxins used in defensive situations, and a lower relative abundance of certain toxins specific to their invertebrate prey (Gangur et al, 2017). This study provided the first evidence for adaptive plasticity in venom compositions, and suggested it has evolved as a mechanism to allow for the optimization of venom use (Gangur et al, 2017).…”
Section: Adaptive Plasticitymentioning
confidence: 99%
“…Repeated periodical encounters with a surrogate vertebrate predator (a taxidermied mouse) over a 6 week period led Hormurus waigiensis to appear to produce a higher relative abundance of some vertebrate specific toxins used in defensive situations, and a lower relative abundance of certain toxins specific to their invertebrate prey (Gangur et al, 2017). This study provided the first evidence for adaptive plasticity in venom compositions, and suggested it has evolved as a mechanism to allow for the optimization of venom use (Gangur et al, 2017). Modification of venom composition in response to environmental pressures could allow scorpions to further optimize venom use in different environments.…”
Section: Adaptive Plasticitymentioning
confidence: 99%
See 2 more Smart Citations